A Novel Tropoloisoquinoline Alkaloid, Neotatarine, from Acorus calamus L. Issue 10 (4th October 2017) - Li, Juan; Li, Zhao‐Xing; Zhao, Jian‐Ping; Wang, Wei; Zhao, Xiao‐Fang; Xu, Bo; Li, Lin; Zhang, Lan; Ren, Jie; Khan, Ikhlas A.; Li, Shun‐Xiang
Abstract : A novel tropoloisoquinoline alkaloid, neotatarine (1 ), was isolated from the 95% ethanol extract of the rhizome parts of Acorus calamus L. The chemical structure was unambiguously elucidated by spectroscopic and single‐crystal X‐ray diffraction analysis. Neotatarine (1 ) exhibited significantly inhibitory activity against A β 25 – 35 induced PC12 cell death with 2, 4 and 8 μm comparing with the assay control ( P < 0.01). Abstract :